Geopolitical analysis of Eastern Mediterranean competitions using game theory - Darvishvand, Hamid (CIMEXUS, 2024)
The Eastern Mediterranean is within the center of a transition period. The- refore, understanding the interests of local and extra-regional actors would help to understand the possible future of this region. Due to its geopolitical significance, this area has developed into a battleground for regional and glo- bal entities that have competing interests. The authorities in the area were motivated to conduct exploratory operations and multilateral cooperation in the Eastern Mediterranean region after new gas resources were found in the waters off the coasts of Egypt and Cyprus. This process led to an increase in Turkey’s, Israel’s, and the neighboring states’ geopolitical activities in the Eastern Mediterranean on both a regional and an international scale. These geopolitical requirements are tied to these nations’ strategic requirements. The goal of this essay was to use game theory to evaluate geopolitically the compe- tition between the Eastern Mediterranean nations and to offer answers to any issues that may have arisen. The research was descriptive-analytical, and the information was gathered through online and library resources, depending on historical material and available proof.